2011
DOI: 10.1104/pp.111.175794
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin Interplay with Ethylene, Auxin, and Glucose Signaling Controls Arabidopsis Seedling Root Directional Growth    

Abstract: (A.M.J.) Optimal root architecture is established by multiple intrinsic (e.g. hormones) and extrinsic (e.g. gravity and touch) signals and is established, in part, by directed root growth. We show that asymmetrical exposure of cytokinin (CK) at the root tip in Arabidopsis (Arabidopsis thaliana) promotes cell elongation that is potentiated by glucose in a hexokinase-influenced, G proteinindependent manner. This mode of CK signaling requires the CK receptor, ARABIDOPSIS HISTIDINE KINASE4 and, at a minimum, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 107 publications
(126 reference statements)
0
67
0
Order By: Relevance
“…The C-terminal motif of APRRs is involved in recognition of certain specific DNA for clock regulation Gendron et al, 2012). Moreover, the response regulators (RRs) accumulate near the lateral roots, where they regulate cytokinin signaling (Mason et al, 2004;Kushwah et al, 2011). Therefore, it is thought that phase reset of the circadian rhythm alters the mecha- nisms controlling plant hormone crosstalk to enable initiation of lateral root differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminal motif of APRRs is involved in recognition of certain specific DNA for clock regulation Gendron et al, 2012). Moreover, the response regulators (RRs) accumulate near the lateral roots, where they regulate cytokinin signaling (Mason et al, 2004;Kushwah et al, 2011). Therefore, it is thought that phase reset of the circadian rhythm alters the mecha- nisms controlling plant hormone crosstalk to enable initiation of lateral root differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…X-Gluc was prepared as 100 mg L 21 stock solution in N,Ndimethylformamide. All treatment concentrations for this study were chosen from previously published reports (Nakamura et al, 2004b;Deslauriers and Larsen, 2010;Kim et al, 2011;Kushwah et al, 2011;Vandenbussche et al, 2011).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Germinated seeds were then covered with a sterile glass coverslip to provide impenetrable obstacle. GUS activities were determined following the methods described previously (Kushwah et al, 2011) after 2 to 3 h for SAUR::GUS and after 4 to 6 h for TCH4::GUS. The experiment was performed three times yielding similar results.…”
Section: Gus Histochemical Stainingmentioning
confidence: 99%
“…Over the years, a number of genes related to root development have been identified that are important for pattern formation, cell cycle, cell growth. Moreover several genes involved in hormonal basis of root development have also been characterized, especially auxin and ethylene (Kushwah et al 2011). Several root mutants have been identified from different plants like Arabidopsis (Busov et al 2008), rice (Kim et al 2007), maize (Hochholdinger et al 2004) wheat (Wang et al 2006) and tomato (Negi et al 2010).…”
Section: Discussionmentioning
confidence: 99%